A comprehensive product line scoping approach and its validation - Schmid, Klaus (Proceedings - International Conference on Software Engineering, 2002)
Product Line Engineering is a recent approach to software development that specifically aims at exploiting commonalities and systematic variabilities among functionally overlapping systems in terms of large scale reuse. Taking full advantage of this potential requires adequate planning and management of the reuse approach as otherwise huge economic benefits will be missed due to an inappropriate alignment of the reuse infrastructure.Key in product line planning is the scoping activity, which aims at focussing the reuse investment where it pays. Scoping actually happens on several levels in the process: during the domain analysis step (analysis of product line requirements) a focusing needs to happen just like during the decision of what to implement for reuse. The latter decision has also important ramifications for the development of an appropriate reference architecture as it provides the reusability requirements for this step.In this paper, we describe an integrated approach that has been developed, improved, and validated over the last few years. The approach fully covers the scoping activities of domain scoping and reuse infrastructure scoping and was validated in several industrial case studies.